Validitas Modul Biofisika Berbasis Model Scientific Reading Based Project (SRBP) Untuk Meningkatkan Kemampuan Critical Thinking Mahasiswa - Zaturrahmi, Zaturrahmi; Nurpatri, Yeni; Muliani, Desy Eka; Indrawati, Ena Suma; Putra, Ilham Adi (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2024)
Students' critical thinking skills need to be practiced from the beginning of learning in school. However, not all learning facilitates the improvement and habituation of critical thinking, causing students' critical thinking skills to be low. Therefore, it is necessary to develop a module that can support the habituation of critical thinking skills, especially for Biophysics courses. This type of research is a development with procedures that refer to the model proposed by Plomp and Nieveen. The module that has been developed is then tested for validity by experts, namely 4 lecturers consisting of 2 lecturers of Physics Education and 2 lecturers of Indonesian Language. Based on the validity test results, it was found that the Biophysics Module based on the Scientific Reading Based Project (SRBP) Model was in the valid category. Thus, it can be concluded that the Biophysics module based on the Scientific Reading Based Project (SRBP) Model can be used to train students' critical thinking skills. After getting the results of the module validity test which was declared valid, then the module that has been developed can proceed to the practicality and effectiveness tests.